Post-TRC prosecutions in South Africa : accountability for political crimes after the Truth and Reconciliation Commission's amnesty process - Bubenzer, Ole (M. Nijhoff, 2009)
This book offers the first comprehensive analysis and evaluation of criminal prosecutions required after the Truth and Reconciliation Commissiona (TM)s amnesty process, putting the issue into a normative and practical perspective of transitional justice in South Africa.